TGF-β and the TGF-β Family: Context-Dependent Roles in Cell and Tissue Physiology - Morikawa, Masato (Cold Spring Harb Perspect Biol, 2016)
The transforming growth factor-β (TGF-β) is the prototype of the TGF-β family of growth and differentiation factors, which is encoded by 33 genes in mammals and comprises homo- and heterodimers. This review introduces the reader to the TGF-β family with its complexity of names and biological activities. It also introduces TGF-β as the best-studied factor among the TGF-β family proteins, with its diversity of roles in the control of cell proliferation and differentiation, wound healing and immune system, and its key roles in pathology, for example, skeletal diseases, fibrosis, and cancer.